Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.5114/aoms.2012.32619
|View full text |Cite
|
Sign up to set email alerts
|

Association of CD36 gene polymorphisms with echo- and electrocardiographic parameters in patients with early onset coronary artery disease

Abstract: IntroductionCD36 plays an important role in long-chain fatty acid homeostasis in skeletal muscle and the myocardium. CD36 deficiency may lead to reduced myocardial uptake of long-chain fatty acid. Therefore, different mutations of the CD36 gene may contribute to the clinical heterogeneity of cardiac hypertrophy.Material and methodsThe objective of the study was to investigate whether there is an association between the sequence changes in CD36 and echocardiographic and electrocardiographic parameters in Caucas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
(33 reference statements)
0
4
0
Order By: Relevance
“…Monika Rać et al . [ 55 ] confirmed that the CD36 gene polymorphisms were involved with echo and electrocardiographic parameters in patients with early onset CHD. Alstrom syndrome 1 ( ALMS1 ) gene polymorphisms were shown to be significantly associated with early-onset MI in both Japanese and Korean populations [ 56 ].…”
Section: Discussionmentioning
confidence: 90%
“…Monika Rać et al . [ 55 ] confirmed that the CD36 gene polymorphisms were involved with echo and electrocardiographic parameters in patients with early onset CHD. Alstrom syndrome 1 ( ALMS1 ) gene polymorphisms were shown to be significantly associated with early-onset MI in both Japanese and Korean populations [ 56 ].…”
Section: Discussionmentioning
confidence: 90%
“…Left ventricular hypertrophy is an important independent predictor of subclinical target organ damage of atherosclerosis disease [11, 12]. Osteoporosis and atherosclerosis are both diseases closely related to aging.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies have also shown that there may be a correlation between the two diseases in the pathophysiological mechanism [79]. Left ventricular hypertrophy (LVH) is a clear independent risk for CVD [1012]. This paper aims to evaluate the correlation between osteoporosis and left ventricular hypertrophy in elderly men.…”
Section: Introductionmentioning
confidence: 99%
“…A deficient state is associated with decreased BMIPP uptake. This defect can be corrected by administering CoQ10 [179][180][181][182][183][184].…”
Section: Connecting Heat Stress To Cardiovascular Disease and Ppcmmentioning
confidence: 99%